2013
DOI: 10.1016/j.neuroscience.2013.06.068
|View full text |Cite
|
Sign up to set email alerts
|

Spinal 5-HT7 receptors and protein kinase A constrain intermittent hypoxia-induced phrenic long-term facilitation

Abstract: Phrenic long-term facilitation (pLTF) is a form of serotonin-dependent respiratory plasticity induced by acute intermittent hypoxia (AIH). pLTF requires spinal Gq protein-coupled serotonin-2 receptor (5-HT2) activation, new synthesis of brain-derived neurotrophic factor (BDNF) and activation of its high-affinity receptor, TrkB. Intrathecal injections of selective agonists for Gs protein-coupled receptors (adenosine 2A and serotonin-7; 5-HT7) also induce long-lasting phrenic motor facilitation via TrkB “trans-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
66
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 65 publications
(108 reference statements)
2
66
1
Order By: Relevance
“…To determine whether PKA is necessary for 5-HT 7 receptor-induced pMF KT-5720, a PKAi (n ϭ 6; 12 l, 100 M), was given prior to 5-HT 7 receptor agonist injections. We previously demonstrated that KT-5720 at this dose prevents PKA-mediated constraint of 5-HT 2A receptor-dependent, AIH-induced pMF (Hoffman and Mitchell 2013). In addition, this dose prevents PKA-but not EPAC-dependent signaling within cell cultures (Davies et al 2000).…”
Section: Methodsmentioning
confidence: 78%
See 4 more Smart Citations
“…To determine whether PKA is necessary for 5-HT 7 receptor-induced pMF KT-5720, a PKAi (n ϭ 6; 12 l, 100 M), was given prior to 5-HT 7 receptor agonist injections. We previously demonstrated that KT-5720 at this dose prevents PKA-mediated constraint of 5-HT 2A receptor-dependent, AIH-induced pMF (Hoffman and Mitchell 2013). In addition, this dose prevents PKA-but not EPAC-dependent signaling within cell cultures (Davies et al 2000).…”
Section: Methodsmentioning
confidence: 78%
“…Although PKA constrains 5-HT 2 receptordependent pMF through cross-talk inhibition (Hoffman and Mitchell 2013), several lines of evidence suggest that EPAC (not PKA) mediates 5-HT 7 receptor-induced pMF. However, no study has attempted to localize these proteins in spinal respiratory neurons in general, or phrenic motor neurons (PMNs) in specific.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations